Fundamental aspects of solid oxide electrolyzer cell modelling and the application for the system level analysis - Stempien, Jan Pawel (2016)
In this work the author discusses the fundamental aspects of modelling Solid Oxide Electrolyzer Cell. The discussion is performed in order to motivate and guide the design of an improved model of SOEC capable of predicting the experimental results in greater accuracy and wider scope. The author proposed a new model including the effects of operating the electrolyzer under the extreme oxygen chemical potential difference, the establishment of equilibrium potential under the co-electrolysis conditions and the effects of electrode’s microstructure on cell performance. The proposed model: predicts a new mode of loss if the cell is run with insufficient fuel, i.e. the short-circuiting of the electrolyzer; decreases prediction error of Open-Circuit Voltage from ~20% to <2% and allows for accurate calculation of OCV for co-electrolysis operation; allows to analyse effects of electrode’s porosity, tortuosity, pore and grain radiuses, thicknesses and active areas on cell’s performance. As defined, the model was applied to analyse several energy conversion systems formulated by the author to address current issues in the energy sector, i.e. mitigation of CO2 emissions, alleviation of renewable energy intermittency, grid balancing, synthetic hydrocarbon fuel production (major fraction of end-user energy consumption). Formulated systems were analysed and optimized with the use of author’s developed model. The systems are divided into two groups, the first designed for CO2 mitigation and grid balancing and the second purposed for synthetic fuel production from renewable electricity and seawater. The first group of systems included analysis of exhaust gases recycling which is crucial for viable operation of SOEC systems without the need for constant external hydrogen delivery. The systems were predicted to achieve ~50% energy conversion efficiency and ~70% CO2 conversion potential. The second group of systems was predicted to achieve efficiency from ~60 to ~90% depending on the produced synthetic fuel and 100% of CO2 conversion. The lower number relates to methanol production and the higher to hydrogen production, other investigated fuels were syngas (89%), methane (81%) and Fischer-Tropsch fuels (67%). The produced Fisher-Tropsch fuels where 31% C1-C4, 36% C5-C17 and the remaining long chained hydrocarbons contributed 33%. The ratio between saturated and unsaturated hydrocarbons for light-distillates was 7.5, for mid-distillates was 11, and for heavy-distillates was 28. The research concluded in this thesis has been disseminated into 7 peer-reviewed journal papers and 1 conference poster.